Exploring fungal potential for microbial-induced calcite precipitation (MICP) in bio-cement production - Devgon, Inderpal; Kumar Sachan, Rohan Samir; Rajput, Khushboo; Kumar, Mukesh; Mohammad Said Al-Tawaha, Abdel Rahman; Karnwal, Arun; Malik, Tabarak (Frontiers in Materials, 2024)
Microbial-induced calcite precipitation (MICP) involves various microorganisms, such as bacteria, fungi, and algae. This study focuses on producing bio-cement using fungal species and selecting potential candidates isolated from alkaline soil of different regions of Punjab, namely Majha, Malwa, and Doaba. The selection of fungi isolates capable of bio-cement production involves several tests, including urease assay and calcium precipitation, Isolates having high urease enzyme production and able to perform calcite precipitation are selected for instrumental analyses such as X-ray diffraction (XRD) and scanning electron microscopy (SEM). The isolates selected for further analysis are S1(3) with 8.879±2.94 , S1(18) with 8.421±0.13, and S4(1) with 10.057±0.45 urease activity and least free calcium ions that are 2.337±0.5, 3.339±0.5 and 4.074±0.1 respectively. The confirmation of calcite precipitation through XRD and FESEM. For XRD the calcite precipitation with sharp crystalline peaks for S1(3), S1(18) and S4(1) are shown and also, the calcite precipitation is evident in the micrographs of FESEM. These combined results confirm the potential of urease-positive fungi to facilitate calcite production, which could lead to bio-cement development in future research.